The book of the new moral world, containing the rational system of society. Complete in 7 parts (Watson, 1849)
Part 1. ...Rational system of society, founded on demonstrable facts, developing the constitution and laws of human nature and of society. London, Home Colonization Society, 1842. XXXII, 80 p